Distribution of High-Sensitivity Troponin Taken Without Conventional Clinical Indications in Critical Care Patients and Its Association With Mortality*. Issue 9 (13th April 2021) - Hinton, Jonathan; Augustine, Maclyn; Gabara, Lavinia; Mariathas, Mark; Allan, Rick; Borca, Florina; Nicholas, Zoe; Beecham, Ryan; Gillett, Neil; Kwok, Chun Shing; Cook, Paul; Grocott, Michael P. W.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To describe the distribution of high-sensitivity troponin in a consecutive cohort of patients in critical care units, regardless of clinical indication, and its association with clinical outcomes. DESIGN: Prospective observational study. SETTING: Single-center teaching hospital. PATIENTS: Consecutive patients admitted to two adult critical care units (general critical care unit and neuroscience critical care unit) over a 6-month period. INTERVENTIONS: All patients had high-sensitivity troponin tests performed at admission and tracked throughout their critical care stay, regardless of whether the supervising team felt there was a clinical indication. The results were not revealed to patients or clinicians unless clinically requested. MEASUREMENTS AND MAIN RESULTS: There were 1, 033 patients in the study cohort (general critical care unit 750 and neuroscience critical care unit 283). The median high-sensitivity troponin was 21 ng/L (interquartile range, 7–86 ng/L), with 560 patients (54.2%) above the upper limit of normal as defined by the manufacturer. Admission high-sensitivity troponin concentrations above the upper limit of normal in general critical care unit and neuroscience critical care unit were associated with increasing age, comorbidity, markers of illness severity, and the need for organ support. On adjusted analysis, the high-sensitivity troponin concentration remained an independent predictor of critical care mortality in general critical care unit and neuroscience critical care unit. CONCLUSIONS: High-sensitivity troponin elevation, taken outside the context of conventional clinical indications, was common in the critically ill. Such elevations were associated with increasing age, comorbidity, illness severity, and the need for organ support. Admission high-sensitivity troponin concentration is an independent predictor of critical care mortality and as such may represent a novel prognostic biomarker at admission.